Ketorolac Tromethamine Improves the Analgesic Effect of Hyoscine Butylbromide in Patients with Intense Cramping Pain from Gastrointestinal or Genitourinary Origin - del Valle-Laisequilla, C. F.; Flores-Murrieta, F. J.; Granados-Soto, V.; Rocha-González, H. I.; Reyes-García, G. (Arzneimittelforschung, 2012)
The symptomatic treatment of pain associated with spasm of gastrointestinal or genitourinary origin can include the use of spasmolytic agents and/or non-steroidal anti-inflammatory drugs. However, the evidence of a superior effectiveness of combination in comparison with individual drugs is scarce and controversial. A double-blind, randomised, clinical trial study was designed to characterize the analgesic effect and safety of ketorolac and hyoscine butylbromide against hyoscine butylbromide alone in patients with ambulatory acute cramping pain of gastrointestinal and genitourinary origin. 160 patients with a pain level ≥4 in a 1–10 cm visual analogue scale were allocated to receive a fixed dose of ketorolac/hyoscine butylbromide (10 mg/20 mg) or hyoscine butylbromide (20 mg) alone at 6 h intervals, during a 48 h period. Both treatments were similarly effective when compared as a whole or when groups were classified by pain origin. Conversely, when treatments were grouped by pain intensity, ketorolac/hyoscine butylbromide combination showed a significant better pain relief profile than hyoscine butylbromide alone in pain intensity ≥7, but not <7. Data indicate that the oral ketorolac/hyoscine butylbromide mixture could be a better option than hyoscine butylbromide alone in the treatment of some acute intense cramping painful conditions.
Keywords: visceral pain; ketorolac; hyoscine butylbromide; spasmolytic; NSAID